Comparison of the Application of E-commerce in Online Versus Offline: Theoretical Review - Rezki Nur Amalia Achmad; Basuki Rachmat (Institut Teknologi Sepuluh Nopember, 2020)
The development of internet technology has positive impact for improving business performance. Social media such as Facebook, Twitter, Instagram can be easily accessed by anyone and enable customers interact with others like face to face communication. Now days, wedding organizer also using social media for marketing activities. Some wedding organizers use Instagram social media as a marketing strategy, because Instagram social media is a way for wedding planners to introduce themselves to the wider community. This study aims to determine the application of E-Commerce affect the perception of ease in the Event Organizer business and determine the application of social media affect the perception of ease in the Event Organizer business. This research uses a qualitative approach with a case study method that will be described descriptively from the results of data collection